Key determinants influencing investor decision in financial markets: Systematic Literature Review - ABDELBAKI, Noureddine; SABHI, Rajae; OUTELLOU, Soumaya (Revue Internationale des Sciences de Gestion, 2023)
Decision research has experienced a significant growth, especially after the inclusion of behavioral factors in the equation. This has led to the rejection of the idea that decision makers are purely rational, but there is still a gap in the literature to understand this phenomenon in the context of financial markets. The objective of this article is to present the notion of decision-making and the theories that explain it, including decision theory, perspective theory, theory of planned behavior, and traditional finance theory. Furthermore, considering that investors play a pivotal role in financial markets and their decisions can have a significant impact, we raise the question of the primary factors that can influence their decision-making process. Thus, this research aims to conduct a theoretical examination basing on sysyematic literature review while trying to define determinants that can influence investors’ decision in financial markets. According to this article, a study of 23 articles from the Google Scholar database revealed the identification of four primary factors that can impact an investor’s decision-making process. In fact, the findings obtained from these results can be advantageous not only for researchers but also for individuals involved in or connected to the financial markets.